FAIR COMPETITION AND PROCUREMENT EFFICIENCY IN THE RIVERS STATE GOVERNMENT MINISTRIES (UNIZIK Journal of Marketing, 2025)
This study examined the relationship between fair competition and procurement efficiency in Rivers State Government ministries. Fair competition was conceptualized as the independent variable, while value for money and public accountability served as measures of procurement efficiency. Two research questions guided the study, which adopted a cross-sectional survey design. The population comprised procurement officers across all 26 ministries in the Rivers State Government ministries. Given the manageable size of the population, a census approach was utilized. Instrument reliability was confirmed using Cronbach’s Alpha, with all items scoring above 0.70. Data were analyzed using descriptive and inferential statistics, and two hypotheses were tested using Spearman’s Rank Order Correlation at a 95% confidence level and a 0.05 significance threshold. Findings revealed a significant positive relationship between fair competition and procurement efficiency within the ministries. The study concludes that promoting fair competition in public procurement processes enhances transparency, reduces costs, and improves value for money and public accountability. It is recommended that stringent procurement policies be implemented to encourage competitive tendering and foster efficient procurement practices across all ministries.
Keywords: Fair competition, Procurement efficiency, Value for money, Public accountability, Transparency